JEJARING KEBIJAKAN DALAM IMPLEMENTASIANGKUTAN BARANG DITEMBILAHAN DITINJAU DARI PERSPEKTIF KELOMPOK SASARAN KEBIJAKAN - Lili Natalia; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The handling of overloads provided by the Tembilahan Transportation Agency is only quoting regional retributions, resulting in an increase in overloaded vehicles every day. in the interests of the general public, especially the damage to road infrastructure as public facilities. Therefore, there is a need for a study of the policies implemented by Indragiri Hilir Regency, especially in Tembilahan in the policy of handling goods transport vehicles that are not in accordance with the provisions of applicable laws and regulations. The purpose of this study is to find out and analyze the policy network in the implementation of freight transportation in Tembilahan in terms of the perspective of the policy target group and the obstacles. The method used are descriptive and qualitative methods; The informants in this study were the Head of the UPT PKB Terminal and Parking of the Indragiri Hilir Transportation Service, the Transportation Section of the Indragiri Hilir Transportation Service, Truck Drivers and the Community. Data collection techniques are interviews, observation and documentation. This study concludes that the results of the study concluded that the policy network in the implementation of freight transport in Tembilahan in terms of the perspective of the policy target group had been implemented quite well. The implementation of the policy for supervising the cargo transportation of goods in Tembilahan refers to the Regulation of the Minister of Transportation of the Republic of Indonesia Number 60 of 2019 concerning the implementation of goods transportation with motorized vehicles on the road. So that the implementation will not run away from the regulation. For this supervisory policy standard, the implementers have followed the standards provided by the regional regulation. Keywords: Network, Policy, Implementation, Freight